THE KORAN IN THE CONTEXT OF LANGUAGE EPISTEMOLOGY - Садов’як, О. Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Methodological ways of researching in text of Koran are being analyzed in this article.